A systematic review of health service interventions to reduce use of unplanned health care in rural areas. Issue 2 (28th October 2015) - Brainard, Julii Suzanne; Ford, John A.; Steel, Nicholas; Jones, Andy P.
Abstract: Rationale, aims and objectives: Use of unplanned health care has long been increasing, and not enough is known about which interventions may reduce use. We aimed to review the effectiveness of interventions to reduce the use of unplanned health care by rural populations. Methods: The method used was systematic review. Scientific databases (Medline, Embase and Central), grey literature and selected references were searched. Study quality and bias was assessed using Cochrane Risk of Bias and modified Newcastle Ottawa Scales. Results were summarized narratively. Results: A total of 2708 scientific articles, reports and other documents were found. After screening, 33 studies met the eligibility criteria, of which eight were randomized controlled trials, 13 were observational studies of unplanned care use before and after new practices were implemented and 12 compared intervention patients with non‐randomized control patients. Eight of the 33 studies reported modest statistically significant reductions in unplanned emergency care use while two reported statistically significant increases in unplanned care. Reductions were associated with preventative medicine, telemedicine and targeting chronic illnesses. Cost savings were also reported for some interventions. Conclusion: Relatively few studies report on unscheduled medical care by specifically rural populations, and interventions were associated with modest reductions in unplanned care use. Future research should evaluate interventions more robustly and more clearly report the results.